THE INVESTIGATIONS OF TOTAL ANTIOXIDANT STATUS AND BIOCHEMICAL SERUM PROFILE IN THYMOQUINONE-TREATED RATS - Kurt, E; Dede, S; Ragbetli, C (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: This study was planned to determine the dosage and duration of thymoquinone (TQ) at which it demonstrates the optimum effect on the total antioxidant status (TAS) and the biochemical parameters in the blood serum. Materials and Methods: 48 male rats (Wistar-albino) weighing between 200-250 g were used as material. Group 1 (control) (TQ solution 5 mg/kg/day), Group 2 (15 mg/kg/day), Group 3 (30 mg/kg/day), Group 4 (45 mg/kg/day) and Group 5 (60 mg/kg/day) were designated, each containing 8 rats. Different doses of TQ (oral gavage) were administered for four weeks. Results: The TAS levels were determined to be considerably low statistically in all TQ-administered groups in comparison with the control group. It was determined that the serum biochemical parameters exerted a significant effect depending on the TQ doses. Conclusion: As a result, rats administered with TQ orally, at 60 mg/kg dosage, show that the liver and kidney function parameters in particular as different from normal. This brings us to the conclusion that at this dosage, there is reliable biochemical wise but future protective studies in which 30 mg/kg doses can be used safely is encouraged.